Narrative review: pengaruh terapi massage counterpressure terhadap pengurangan nyeri dalam persalinan - Hutari Puji Astuti; Andari Wuri Astuti; Dinar Agustin; Hardiyanti Fitrah Awaliyah; Gana Rendra Winarti; Vanny Oktaviani Jaya (Jurnal Cakrawala Promkes, 2021)
Labor often prompts unpleasant, fearful, or, further, traumaticexperiences due to the pain it entails. Scientific evidence suggests thatpain during labor can be managed using two methods; pharmacologicaland non-pharmacological. Pharmacology is a method of using drugs,whereas non-pharmacologic is without the administration of drugs. The nonpharmacologicalmethod is known as complementary and alternativetherapies, one practice is through massage. Massage frequentlyperformed to reduce labor pain is counterpressure. The purpose of thisstudy is to investigate the effect of counterpressure massage therapy asa measure to reduce labor pain. The method used is a narrative review.Article exploration was carried out in several databases, which arePubmed and Science Direct. In the case of Gray Literature, it wasaccessed via Google Scholar. Specific keywords were employed forliterature search and articles were selected by considering inclusion andexclusion criteria. The article selection process was elaboratedtransparently in the PRISMA Flowchart. From the article selectionprocedure, 14 articles were identified and fulfilled the criteria. Thus,articles were critically analyzed (Critical Appraisal) using the MixedMethod Appraisal Tool (MMAT). The review concludes thatcounterpressure is a massage performed by applying continuouspressure to the patient's sacral with the heel of the hand or fist of thehand. Counterpressure massage can be done in a straight stroke or smallcircular stroke. This technique is proven to be sufficient in relieving backpain during labor. The recommendation suggested is based on the 14articles reviews carried out that a common problem occurring in laboringwomen is physiological pain experience during childbirth so that it mayprovoke bad experiences for mothers, especially fear and anxiety thatmay lead to prolonged labor.Labor often prompts an unpleasant, fearful, or, further, traumatic experiences due to the pain it entails. Scientific evidence suggests that pain during labor can be managed using two methods; pharmacological and non-pharmacological. Pharmacology is a method of using drugs, whereas non-pharmacologic is without the administration of drugs. Non-pharmacological method is known as complementary and alternative therapies, one practice is through massage. Massage frequently performed to reduce labor pain is counterpressure. The purpose of this study is to investigate the effect of counterpressure massage therapy as a measure to reduce labor pain. The method used is a narrative review. Article exploration was carried out in several databases, which are Pubmed and Science Direct. In the case of Gray Literature, it was accessed via Google Scholar. Specific keywords were employed for literature search and articles were selected by considering inclusion and exclusion criteria. The article selection process was elaborated transparently in the PRISMA Flowchart. From the article selection procedure, 14 articles were identified and fulfilled the criteria. Thus, articles were critically analyzed (Critical Appraisal) using the Mixed Method Appraisal Tool (MMAT). The review concludes that counterpressure is a massage performed by applying continuous pressure to the patient's sacral with the heel of the hand or fist of the hand. Counterpressure massage can be done in a straight stroke or small circular stroke. This technique is proven to be sufficient in relieving back pain during labor. The recommendation suggested is based on the 14 articles reviews carried out that a common problem occurring in laboring women is physiological pain experience during childbirth so that it may provoke bad experiences for mothers, especially fear and anxiety that may lead to prolonged labor